P3.72 The prevalence of anal high-risk human papillomavirus infections and associated risk factors in men-who-have-sex-with-men in cape town, south africa. (8th July 2017) - Müller, EE; Rebe, K; Chirwa, TF; Struthers, H; McIntyre, J; Lewis, DA
Abstract : Introduction: We investigated the prevalence of high-risk (HR) human papillomavirus (HPV) infections and associated behavioural risk factors in men-who-have-sex-with-men (MSM) attending a clinical service in Cape Town, South Africa. Methods: MSM were enrolled at the Ivan Toms Centre for Men's Health in Cape Town. For each participant, a psychosocial and sexual behavioural risk questionnaire was completed and an anal swab was collected and tested for 13 HR-HPV types using the Linear Array HPV Genotyping Test. Logistic regression analyses were performed to determine sexual risk factors associated with anal HR-HPV infection. Results: The median age of the 200 participants was 32 years (IQR 26–39.5), of which 31.0% were black, 31.5% mixed race and 35.5% white. The majority of the participants (73.0%) had completed high school, 42.0% had a tertiary level qualification and 69.0% were employed. The prevalence of HR-HPV types was 57.6% [95% CI: 50.3%–64.7%] in anal samples, with HPV-16 being the most common HR-HPV type detected (22.0%). HPV types 16 and/or 18, the only HR-HPV types included in all available HPV vaccines, were detected in 55 (28.8%) [95% CI: 22.5%–35.8%] anal specimens. Furthermore, 95 (49.7%) [95% CI: 42.9%–57.1%] specimens had one or more HR-HPV types included in the 9-valent HPV vaccine. Among the 88 MSM (44.0%) that were HIV positive, 81.2% [95% CI: 71.2%–88.8%] had anal HR-HPV ( p =0.001). Factors that were independently associated with having anal HR-HPV infection included having sex with men only, ever engaging in group sex, living with HIV and practising receptive anal intercourse. Conclusion: HR-HPV infections in the anal canal were common among MSM in Cape Town with the highest HR-HPV burden among HIV co-infected MSM, men who have sex with men only and those that practised receptive anal intercourse. Behavioural intervention strategies and targeted HPV vaccination of young MSM are urgently required to address the high prevalence of oncogenic HPV and HIV co-infections among MSM in South Africa.